Alligator tails and crocodile cakes - Moon, Nicola; Ellis, Andy (New York : Kingfisher, 2000)
High-spirited Alligator and his patient friend Crocodile play hide-and-seek and bake a cake.
Keywords: Alligators -- Fiction; Crocodiles -- Fiction; Hide-and-seek -- Fiction; Baking -- Fiction; Cleanliness -- Fiction; Friendship -- Fiction